The Relationship between Big Five Personality Traits and Academic Performance in Medical Students - Charan Kishor, Shetty; Ab. Aziz, Sulaiman; Khairi, Che Mat; Myat Moe Thwe, Aung; Rohayah, Husain; Vidya, Bhagat (2019)
It is a learned fact that personality is an integration of individuals' characteristics that benefits them to stay successful in their career path. ln the field of education the educators, researchers, and psychologists are on the constant explosion of the tightfisted set of variables that predicts patterns of students' behaviors and their association with academic achievement. Thus the current study aimed done at finding about the relationship between 'Big Five' personality traits and academic achievement of undergraduate medical students. The total sample of 122 from year one and two medical students of Universiti Sultan Zainal Abidin, Malaysia was involved in the study. All personality traits positively and significantly predicted students overall grade. Of all traits, Openness and Neuroticism were positively related to student's academic achievement than agreeableness, and conscientiousness and are more important predictors of overall grade of the students. Extraversion was positively related (r =.150) but not statistically significant. The present results provide evidence supporting the Relationship between Personality Traits and Academic Performance in medical students.